HUBUNGAN ANTARA DEPRESI DAN MEROKOK PADA SISWA SEKOLAH MENENGAH PERTAMA DI JAKARTA - Anthea Casey; Herlina Uinarni; Eva Suryani; Dharmady Agus (Bahasa Indonesia, 2021)
Introduction: The number of depressed adolescent and adolescent smoker in Indonesia has increased quite dramatically. The literature suggests that smokers are more likely to be depressed, while depressed people are more likely to smoke. Objective: The purpose of this study was to determine the association between depression and smoking among junior high school students in Jakarta. Methods: A cross-sectional analytic study was conducted at junior high school in Central Jakarta. In total, 407 students, grade 9 to 11 were participated (47.9% males and 52.1% females). Questionnaires on depression and smoking were distributed, including BDI-II questionnaire for depression which had been validated into Indonesian language, and questionnaire for smoking assessed by using single question that classified the respondents’ smoking habit as daily smoker, irregular smoker, former smoker, and nonsmoker. Results: This study revealed a significant association between depression and smoking in junior high school students (p=0.000, OR=2.502). Among 30.2% students who were depressed, 2.5% were daily smokers, 5.4% were irregular smokers, 10.8% were former smokers, and 11.5% were nonsmokers. Conclusion: Depression increases the risk of smoking by 2.5 times in adolescents, suggesting that smoking prevention may need to be combined with depression prevention and treatment.